One Health in a Digital World: Technology, Data, Information and Knowledge - Scott, Philip; Adedeji, Taiwo; Nakkas, Haythem; Andrikopoulou, Elisavet (Yearbook of Medical Informatics, 2023)
Objectives: To describe the origins and growth of the One Health concept and its recent application in One Digital Health.Methods: Bibliometric review and critical discussion of emergent themes derived from co-occurrence of MeSH keywords.Results: The fundamental interrelationship between human health, animal health and the wider environment has been recognized since ancient times. One Health as a distinct term originated in 2004 and has been a rapidly growing concept of interest in the biomedical literature since 2017. One Digital Health has quickly established itself as a unifying construct that highlights the critical role of technology, data, information and knowledge to facilitate the interdisciplinary collaboration that One Health requires. The principal application domains of One Digital Health to date are in FAIR data integration and analysis, disease surveillance, antimicrobial stewardship and environmental monitoring.Conclusions: One Health and One Digital Health offer powerful lenses to examine and address crises in our living world. We propose thinking in terms of Learning One Health Systems that can dynamically capture, integrate, analyse and monitor application of data across the biosphere.
Keywords: One health; informatics; health policy; global health; learning health system